PERAN PSIKOLOGI PENDIDIKAN DALAM PEMBELAJARAN PAI - Saidah, Elbina Mamla (STAI Hubbulwathan Duri, 2016)
In learning process, most of students use behaviorism theory. It emphasizes on stimulus and response. The students compete with others because of that situation. Here, the most important thing is students’ memory. Learning process need memory because the process put a lot of memorization. It has the goal of keeping the students’ attitude changed from not knowing to knowing. Application of the principles of educational psychology is very important to enable the development of students optimally